THE EVOLVE PROGRAM: A PSYCHO-SOCIAL INTERVENTION PROGRAM FOR TARGETED VIOLENCE - Michael King (The Journal of Intelligence, Conflict and Warfare)
On November 19, 2024, Dr. Michael King presented The Evolve Program: A Psycho-Social Intervention Program for Targeted Violence for this year’s West Coast Security Conference. The key points discussed were the positive impact that providing psychosocial support had on reducing extremist beliefs in participants, the importance of building a trusting relationship with participants, and that the program is available for free to anyone needing assistance in Alberta, Saskatchewan, or Manitoba.